Gender-Specific Effect of 5-HT and 5-HIAA on Threshold Level of Behavioral Symptoms and Sex-Bias in Prevalence of Autism Spectrum Disorder - Chakraborti, Barnali; Verma, Deepak; Guhathakurta, Subhrangshu; Jaiswal, Preeti; Singh, Asem Surindro; Sinha, Swagata; Ghosh, Saurabh; Mukhopadhyay, Kanchan; Mohanakumar, Kochupurackal P.; Rajamma, Usha (Frontiers in Neuroscience, 2020)
Platelet hyperserotonemia in a subset of Autism Spectrum Disorder (ASD) probands, efficacy of selective serotonin reuptake inhibitors (SSRIs) in reducing behavioral deficits and gender-bias in normal serotonin (5-hydroxy tryptamine or 5-HT) synthesis suggest disruption in stringent regulation of serotonin metabolism in ASD. Therefore, we investigated the changes in 5-HT and 5-hydroxy indole acetic acid (5-HIAA) in ASD probands to assess its effect on the behavior of male and female probands. ASD cases (n = 215) were examined using childhood autism rating scale (CARS). Platelet 5-HT (104 cases and 26 controls) and platelet/plasma 5-HIAA (73 cases and 17 controls) were estimated using high performance liquid chromatography coupled with electrochemical detector (HPLC-ECD). In male probands, we observed increase in platelet 5-HT content in association with increase in the score for adaptive responses and increase in platelet 5-HIAA levels with concomitant decline in the score for intellectual response. Age did not influence the neurochemical parameters, but imitation, listening responses and nonverbal communication scores decreased with age. Conversely in female probands, plasma 5-HIAA level significantly attenuated with age, when platelet 5-HT content remained unchanged. Interestingly, platelet/plasma 5-HT and plasma 5-HIAA were higher in female controls. Female probands displayed severe autism-associated behaviors. Overall results indicate gender-bias in 5-HT and 5-HIAA regulation, which probably increases the threshold level of ASD phenotypes in the females, thereby affecting ASD prevalence in a sex-specific manner.